Mechanisms of wound healing and gastro protective effects of ethanol leaf extract of Jasminum Sambac and Hemigraphis Colorata on HCL/ethanol-induced gastric injury in experimental animals / Ahmed Salim Ahmed Al Rashdi - Ahmed Salim, Ahmed Al Rashdi (2013)
Sprague Dawley rats weighing 225-250 g were used for evaluating wound healing and gastroprotective activities. The plant extracts of J.sambac and H.colorata were assessed in-vivo for toxicity study. Antioxidant properties of the crude extracts were determined using DPPH radical scavenging assay and total phenolic content. Β-sitosterol and octyl gallate compounds were isolated from J. sambac and H. Colorata petroleum ether crude extracts by CC, TLC and HPLC and were evaluated for their gastroprotective activities.Macroscopic finding showed that H.colorata and J.sambac significantly accelerated wound healing compared to vehicle. Post wounding tissues collected on day 10th for oxidative damage evaluation revealed significant increase in antioxidant enzymes (SOD and GPx) and decrease in the MDA level. Grossly, and histology showed smooth surfaces, marked reduction of edema and leucocytes infiltration of submucosal layer compared with ulcer group. Immunohistochemistry revealed overexpression of Hsp70 protein and downexpression of Bax protein in rats. Significant increase in the pH, mucus of gastric content and gastric PGE2, SOD, COX -2 and reduced level of MDA were observed. Β-sitosterol compound showed significant gastroprotective activity against acidified ethanol-induced gastric damage in rats more than Octyl gallate compound. Moreover, β-sitosterol recorded significant increase in the pH, gastric mucus and decrease in the ulcer area. Biochemistry, histopathology and immunohistochemistry results revealed significant improvement in β-stosterol than Octyl gallate.Wound healing can be accelerated and gastric ulcer can be inhibited by the antioxidants activity of H.colorata and J.sambac leaves extracts and its active antioxidant ingradient β-sitosterol while the normal gastric status can be preserved.